Mobile learning in the higher education / Abd Rasyid Ramli ... [et al.] - Ramli, Abd Rasyid; Md Zani, Rosliza; Ali, Norhidayah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Mobile learning, also known as m-learning, has become a new revolution of learning using mobile devices. Mobile learning enables users a continuous and vast access to the learning process. This can be performed using devices like hand phones, laptops or tablets. Mobile learning or m-learning is considered as the future form of e-learning using mobile technology to enable students to perform their learning process anywhere, any time at their convenience. The traditional e-learning system has two main types; one is of pedagogical services such as learning materials and the other is of information services such as admission, notification and registration. The use of m-learning is growing rapidly in the higher education environment due to its dynamic nature.